Estimating merchantable volume for deciduos trees - Trincado, Guillermo; Von Gadow, Klaus; Sandoval, Victor (Bosque (Valdivia), 1997)
The paper presents an application of two methods of estimating merchantable volume in deciduos trees. The first method uses a volume ratio equation system and the second a taper equation. Compatibility for deciduos trees is achieved with modifications and/or transformations of the models. Suggestions for a practical application in form of code-programs for a correct utilization of proposed models are given.